MEDIA LITERACY AND SOCIAL INCLUSION - Marcellino, Kevin; Irwansyah, Irwansyah (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
Media literacy is the ability to analyze, evaluate, codify, and produce media. Media literacy is able to be a means of protecting media messages, Media literacy is also able to empower audiences to be able to critically view the messages produced by the media. By using a qualitative method with a meta-analysis approach, the research provides additional concepts that can be used in learning media literacy in Indonesia. This study also provides an overview of the existing media literacy in Indonesia. With an emancipatory learning approach and social inclusion, media literacy becomes more capable of building critical awareness and active public participation in the media. Media literacy in Indonesia still lacks emancipatory learning and social inclusion. This needs to be a concern for media literacy education in Indonesia because the Indonesian people are people who actively use the media. Media literacy based on social inclusion and emancipation is able to empower the Indonesian people with existing media messages.  To cite this article (7th APA style): Irwansyah & Marcellino, K. (2021). Media Literacy and Social Inclusion. Journal Communication Spectrum: Capturing New Perspectives in Communication 11(2), 119-126. https://doi.org/10.36782/jcs.v11i2.2171